Negotiating Intersecting Precarities: COVID-19, Pandemic Preparedness and Response in Africa. Issue 1 (2nd January 2022) - MacGregor, Hayley; Leach, Melissa; Akello, Grace; Sao Babawo, Lawrence; Baluku, Moses; Desclaux, Alice; Grant, Catherine; Kamara, Foday; Martineau, Fred; Yei Mokuwa, Esther; Parker, Melissa; Richards, Paul; et al.
ABSTRACT: This article shares findings on COVID-19 in Africa across 2020 to examine concepts and practices of epidemic preparedness and response. Amidst uncertainties about the trajectory of COVID-19, the stages of emergency response emerge in practice as interconnected. We illustrate how complex dynamics manifest as diverse actors interpret and modify approaches according to contexts and experiences. We suggest that the concept of "intersecting precarities" best captures the temporalities at stake; that these precarities include the effects of epidemic control measures; and that people do not just accept but actively negotiate these intersections as they seek to sustain their lives and livelihoods.